Fanworms: Yesterday, Today and Tomorrow - Capa, María; Kupriyanova, Elena; Nogueira, João Miguel de Matos; Bick, Andreas; Tovar-Hernández, María Ana (Diversity, 2021)
Sabellida Levinsen, 1883 is a large morphologically uniform group of sedentary annelids commonly known as fanworms. These annelids live in tubes made either of calcareous carbonate or mucus with agglutinated sediment. They share the presence of an anterior crown consisting of radioles and the division of the body into thorax and abdomen marked by a chaetal and fecal groove inversion. This study synthesises the current state of knowledge about the diversity of fanworms in the broad sense (morphological, ecological, species richness), the species occurrences in the different biogeographic regions, highlights latest surveys, provides guidelines for identification of members of each group, and describe novel methodologies for species delimitation. As some members of this group are well-known introduced pests, we address information about these species and their current invasive status. In addition, an overview of the current evolutionary hypothesis and history of the classification of members of Sabellida is presented. The main aim of this review is to highlight the knowledge gaps to stimulate research in those directions
World Polychaeta Database (WPolyDb)